UPAYA GURU DALAM MENINGKATKAN MINAT BACA CERITA PADA SISWA KELAS III UPTD SD NEGRI DULOLONG BARAT KECAMATAN ALOR BARAT LAUT KABUPATEN ALORTAHUN PELAJARAN 2024/2025 - Lapung, Marwati; Lapung, Jamra; Amsidi, Mukmin (STKIP Muhammadiyah Kalabahi, 2025)
The research aims to describe the teacher's efforts to increase interest in reading stories in class III students at Dulolong Barat State Elementary School. This research is a descriptive type of qualitative research. The subjects of this research were 1 class teacher and 15 class III students at Dulolong Barat State Elementary School. Data collection techniques use observation and interviews. Data analysis techniques in this research use data reduction, data presentation, and drawing conclusions. Data validity techniques and research stages. The results of this research show that teachers' efforts to increase interest in reading stories at West Dulolong State Elementary School, namely: (1) Encouraging children to tell stories about what they have heard or read, (2) Buying books that interest them in reading, (3) Exchanging books with friends, (4) Giving books as gifts, (5) Providing time to read during the learning process, teachers encourage students to increase their interest in reading. One way is by the teacher asking students to go to the library during break time to borrow books that the students like. Class III students' interest in reading stories was aimed at several students visiting the library to borrow books or read books during break times.